(untitled) - Starr, Cecie (Belmont, CA, 2008)
This introductory biology text helps you master biology while encouraging you to think about critical issues. The issues-oriented approach enlivens the subject matter and helps you grasp concepts by making connections between biology and real-life concerns. Here's how it works: An "Impacts, Issues" case study opens each chapter, focusing on a biology-related societal issue. You also view a short film that expands on the issue. Then each chapter's "How Would You Vote?" question, inspired by the case study, asks you to consider biology-related news, explore the facts behind the issue, apply your knowledge of biology, and cast a vote on the Web. You can also see state and nationwide voting tallies. This book has been widely praised for clear and engaging writing, art with step-by-step callouts, and terrific support from student media that all work together to help you "get" biology. Technology highlights include CengageNOW, an interactive online resource featuring personalized study plans and hundreds of animations, and an MP3 download of audio study tools that let you review concepts from the text anywhere!
Keywords: Biology,Human biology,Sinh học,Sinh học người